2021
DOI: 10.19044/esj.2021.v17n12p160
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Mobile Marketing in the Telecommunication Industry of Tanzania: The Effects of Perceived Usefulness, Ease of Use, and Customer’s Knowledge

Abstract: This paper focuses on identifying the factors affecting customer’s adoption of mobile marketing by examining the effects of perceived usefulness, perceived ease of use, and perceived customer’s knowledge in the telecommunications industry of Tanzania. The study extended the Technology Acceptance Model (TAM), with Diffusion of Innovation Theory (DOI), in predicting the customer’s mobile marketing adoption. Survey strategy was employed in data collection by administering the structured questionnaires and collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Furthermore, researchers Meyliana and Fernando (2019) found that perceived usefulness is determined by the factor of trust in the use of fintech services. In the same way, Chille et al . (2021) determined that perceived trust is a significant and positive factor contributing to adopting fintech in marketing.…”
Section: Analysis and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, researchers Meyliana and Fernando (2019) found that perceived usefulness is determined by the factor of trust in the use of fintech services. In the same way, Chille et al . (2021) determined that perceived trust is a significant and positive factor contributing to adopting fintech in marketing.…”
Section: Analysis and Discussionmentioning
confidence: 74%
“…In the same way, Chille et al (2021) determined that perceived trust is a significant and positive factor contributing to adopting fintech in marketing. In relation to the impact of the social norm, the findings agree with a study by Geber and Friemel (2022) that found that social norms influenced the adoption of technology and apps.…”
Section: Path Coefficients Estimated Resultsmentioning
confidence: 95%
“…Their study showed that in mobile marketing applications, performance is the most important factor of user trust. A study in Tanzania by Chille et al (2021) indicated that there is a positive effect on trust and mobile marketing in Tanzania. Customers not only use mobile marketing platforms to make purchases, but at the same time, they also require protection for their security and privacy.…”
Section: Mobile Marketingmentioning
confidence: 99%
“…Telecom companies provide M-payment services due to the fast growth of digital technology and the rise in demand for easy payment methods (Abd-Elrahman et al , 2020). The telecom sector has access to a sizable market, providing a unique opportunity for the major telecom service providers to offer simplified, end-to-end client experiences (Abd-Elrahman et al , 2020; Chille et al , 2021). Telecom companies could use the results to enhance customer satisfaction based on quality services.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Telecom companies could use the results to enhance customer satisfaction based on quality services. Telecom service providers might significantly boost consumer satisfaction if they integrate M-payment capability into their network (Abd-Elrahman et al , 2020; Chille et al , 2021). These M-payment services are provided through dedicated software such as BibiMoney in the telecom sector.…”
Section: Research Implicationsmentioning
confidence: 99%